Aplikasi Tes Jenis Kepribadian Berbasis Android menggunakan Metode MBTI dan DISC - Muhammad Abdul Mukhlis; Tri Listyorini; Mukhamad Nurkhamid (Politeknik Negeri Cilacap, 2021)
Personality is basically owned by everyone and is different from one another. People always want to know about themselves, how and where their interests and needs are. This is one of the reasons why individual personality tests are conducted. Personality test is a set of test tools designed to describe how someone behaves. The method used by psychologists to determine the personality type of an individual is the Myers-Briggs Type Indicator method or commonly called the MBTI test, this test is used to determine the types of human personality. Personality tests besides MBTI, personality tests that are usually used to determine a person's personality type are the DISC (Dominance Influence Steadiness, Conscientiousness) test and also the Four Personality test which includes Sanguinist, Chronic, Melancholic and Plegmatic personality types. These three tests are used and chosen because they are the most widely used tests worldwide for determining human personality. The results of this research will be able to form a system that can help determine the type of human personality using the MBTI and DISC methods